The Effect of Seed-Borne Fungi and Epichloë Endophyte on Seed Germination and Biomass of Elymus sibiricus - Li, Xiu-Zhang; Song, Mei-Ling; Yao, Xiang; Chai, Qing; Simpson, Wayne R.; Li, Chun-Jie; Nan, Zhi-Biao (Frontiers in Microbiology, 2017)
The interactive effects of asexual Epichloë (formerly known as Neotyphodium) endophytes isolated from Hordeum brevisubulatum, Elymus tangutorum and Achnatherum inebrians, and seed-born fungi on Elymus sibiricus seeds, were determined by an in vitro study using supernatents from liquid cultures of the endophyte strains. In an eight week greenhouse study, the effects on seed imbibing the supernatents prior to sowing on the growth of seedlings was measured. The in vitro study was carried out with the seed-borne fungi Alternaria alternaria, Bipolaris sorokinianum, Fusarium avenaceum and a Fusarium sp. isolated from Elymus sibiricus. Different concentrations and combinations of the liquid cultures of endophytic fungi enhanced the interim germination, germination rate, length of coleoptile and radicle, and seedling dry weight of E. sibiricus seeds under stress from seed-borne fungi. In the greenhouse study, different concentrations of the supernatant of the endophytes from H. brevisubulatum and E. tangutorum but not A. inebrians, signficantly (P<0.05) enhanced E. sibiricus seed germination. There was no signficant (P>0.05) increase of the tiller numbers after 2 weeks. However, later on, there were signficant (P<0.05) increases in tiller number (4-8weeks), seedling height (2-8weeks) and dry weight (2-8weeks). The application of Epichloë endophyte culture supernatants was an effective strategy to improve seed germination and growth under greenhouse conditions.